Особливості моторики дітей молодшого шкільного віку з депривацією слуху в процесі фізичного виховання = Features motor skills of children of primary school age deprivation hearing in the process physical education - Savlyuk, Svetlana (Journal of Education, Health and Sport, 2016)
Savlyuk S. Особливості моторики дітей молодшого шкільного віку з депривацією слуху в процесі фізичного виховання = Features motor skills of children of primary school age deprivation hearing in the process physical education. Journal of Education, Health and Sport. 2016;6(9):818-831. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.159358 http://ojs.ukw.edu.pl/index.php/johs/article/view/3904 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 02.09.2016. Revised 24.09.2016. Accepted: 24.09.2016. УДК 159.9 : 616. 28-008.13/.14 ОСОБЛИВОСТІ МОТОРИКИ ДІТЕЙ МОЛОДШОГО ШКІЛЬНОГО ВІКУ З ДЕПРИВАЦІЄЮ СЛУХУ В ПРОЦЕСІ ФІЗИЧНОГО ВИХОВАННЯ Features motor skills of children of primary school age deprivation hearing in the process physical education С. Савлюк Національний університет фізичного виховання і спорту України, м. Київ S. Savlyuk National University of Physical Education and Sports of Ukraine, m. Kyiv Анотація. Мета дослідження: розкрити особливості моторики дітей молодшого шкільного віку з депривацією слуху (ДС) спеціальної школи-інтернату у процесі фізичного виховання.Матеріал і методи: дослідження силових якостей дітей молодшого шкільного віку з депривацією слуху проводилися на базі Острозької та Калушської спеціальної загальноосвітньої школи-інтернату І-ІІІ ступенів та ЗОШ № 27 м. Рівне. У дослідженнях узяли участь 139 школярів 6-10 років із депривацією слуху та 186 практично здорових однолітків того ж віку. Результати: виявлене значне відставання дітей із депривацією слуху від їх ровесників: у хлопчиків і дівчаток 6-10 років із ДС показники динамометрії, рівень розвитку сили м’язів черевного пресу та cилового індексу статистично вірогідно нижчі, ніж у практично здорових однолітків (р<0,01). Висновки: визначені показники cилових якостей дітей із ДС статистично вірогідно нижчі у 2-3 рази, ніж у їх здорових однолітків. Ключові слова: силові, якості, депривація, слух, моторика, молодший, школяр. Аннотация. Цель исследования: исследовать моторику детей младшего школьного возраста с депривацией слуха (ДС) специальной школы-интерната в процессе физического воспитания.Материал и методы: исследование силовых качеств детей младшего школьного возраста с депривацией слуха проводилась на базе Острожской и Калушской специальной общеобразовательной школы-интерната І-ІІІ степеней и СОШ № 27 г. Ровно. В исследованиях приняли участие 139 школьников 6-10 лет с депривацией слуха и 186 практически здоровых ровесников того же возраста. Результаты: выявлено значительное отставание детей с депривацией слуха от их ровесников: у мальчиков и девочек 6-10 лет из ДС показатели динамометрии, уровень развития силы мышц брюшного пресса и cилового индекса статистически достоверно ниже, чем у их практически здоровых ровесников (р<0,01). Выводы: определенные показатели cилових качеств детей из ДС статистически достоверно ниже в 2-3 раза, чем у их здоровых ровесников. Ключевые слова: силовые, качества, депривация, слух, моторика, младший, школьник. Annotation. Objective: to investigate the motility of primary school children with hearing deprivation (HD) of special boarding school during physical education.Material and methods: the study of power quality of primary school children with hearing deprivation held at the Ostroh and Kalush special boarding schools of I-III degree and school number 27 c. Rivne. In the study involved 139 students 6-10 years with hearing deprivation and 186 healthy peers of the same age. Results: it was found a significant backlog of children with hearing deprivation from their healthy peers; defined characteristics of power quality of children with HD statistically significantly lower in 2-3 times than in their healthy peers.Conclusions: defined characteristics of the power quality of children with HD are statistically significantly lower in 2-3 times than in their healthy peers. Keywords: power, quality, deprivation, hearing, motor skills, junior, student.